Media Kampanye Sosial Yoga Sebagai Upaya Pencegahan Skoliosis Pada Remaja Perempuan Kota Palembang - Adellia Rihadatulaisy; Bobby Halim; Didiek Prasetya (VisArt: Jurnal Seni Rupa dan Design, 2026)
The development of a sedentary lifestyle among adolescents in the digital era, such as prolonged sitting and excessive gadget use, may contribute to postural problems, including scoliosis. Scoliosis is a spinal disorder that is more commonly found among adolescent girls. Screening results among students at SMP Negeri 35 Palembang showed that 35.4% of respondents were at risk of scoliosis, indicating the need for early preventive efforts through increased awareness of postural health. This design aims to develop an educational, informative, and persuasive social campaign to increase awareness among adolescent girls in Palembang about scoliosis prevention through Hatha Yoga. The design method used is Design Thinking, consisting of the empathize, define, ideate, prototype, and test stages. Data were collected through observation, questionnaires, interviews, and literature studies. The resulting social campaign is based on Visual Communication Design and utilizes both print and digital media to educate the target audience about the importance of maintaining proper posture and practicing Hatha Yoga as a preventive effort against scoliosis